TRANSLATION OF JAPANESE MODALITY INTO INDONESIAN - Adis Kusumawati; Trilia Kartikasari (Jurnal Kata, 2024)
The translation of the modalities contained in a literary work needs to be done with consideration.This is caused by the modalities used to express the speaker's feelings will be different in each language. This paper discusses the translation of modalities contained in Japanese novels Kimi no Suizō wo Tabetai, which are translated into Indonesian.In fulfilling the objectives of the study, descriptive analysis was applied, and all stages of analysis were done qualitatively.The findings of this study reveal that Japanese modalities can be translated in Indonesian into three ways. First, the modality is translated into similar modalities in Indonesian. Second, the modalities are translated into Indonesian using different modalities. Third, Japanese modalities that cannot be translated into Indonesian are translated in the basic form without modality markers. Translation of modalities which are translated into different modalities mostly occurs in deontic modality which is translated into intentional modality. This happens because the translator wants to refine the command into a request or permission by adding the words please ‘tolong’, (can’t you) try ‘coba’ and bisakah ‘can’t you’.  In translating modalities, things that must be considered apart from equivalence are the level of politeness, the relationship between the speaker - the interlocutor, and the level of formality.